2022
DOI: 10.33860/pjpm.v3i3.1256
|View full text |Cite
|
Sign up to set email alerts
|

Pelatihan Pemanfaatan Terapi Komplementer sebagai upaya Penanganan Dismenorhoe pada Remaja Putri

Abstract: Most women who have menstruated often experience menstrual pain (dysmenorrhea). As many as 12.5% ​​of teenage girls in Denpasar have been absent from school activities due to their dysmenorrhea. Other studies have shown that untreated dysmenorrhea will cause problems such as absenteeism from school, decreased academic achievement, adolescents tend to withdraw from relationships, and restrictions on daily activities. The purpose of this service activity is to increase the knowledge, understanding, and skills of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 8 publications
(8 reference statements)
0
2
0
Order By: Relevance
“…Dysmenorrhea pain, described as moderate to severe, significantly affects daily activities and learning abilities of young women (Azzahroh, Indrayani, & Lusiana, 2022;Karout et al, 2021). Pharmacological treatment, such as analgesic drugs, is commonly used, but non-pharmacological approaches are considered easier and have fewer side effects (Andanawarih et al, 2020;Jamhariyah et al, 2021;Nugraha, 2021;Sholihah & Azizah, 2020;Sibero, Sari, & Asmita, 2022;Sumiaty et al, 2022).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Dysmenorrhea pain, described as moderate to severe, significantly affects daily activities and learning abilities of young women (Azzahroh, Indrayani, & Lusiana, 2022;Karout et al, 2021). Pharmacological treatment, such as analgesic drugs, is commonly used, but non-pharmacological approaches are considered easier and have fewer side effects (Andanawarih et al, 2020;Jamhariyah et al, 2021;Nugraha, 2021;Sholihah & Azizah, 2020;Sibero, Sari, & Asmita, 2022;Sumiaty et al, 2022).…”
Section: Methodsmentioning
confidence: 99%
“…The Pantoloan Health Center is one of three Community Health Centers in Palu City that has formed a youth Posyandu but is still lacking in activities related to disseminating information on adolescent reproductive health, especially related to menstrual disorders and how to deal with them (Sumiaty, et al, 2021). A preliminary study conducted on 30 adolescents at the Adolescent Integrated Health Center, Pantoloan Public Health Center found that 77% of adolescents ignored the problem of dysmenorrhea, 85% chose non-pharmacological therapies such as warm compress, ginger tea infusion, and exercise to treat dysmenorrhea, 90% did not understand how to deal with dysmenorrhea, and 82% were absent from school when experiencing dysmenorrhea (Sumiaty, Sakti, & Hasnawati, 2022). This study aimed to determine the effect of effleurage massage on the pain scale of dysmenorrhea in adolescents.…”
Section: Introductionmentioning
confidence: 99%